UPAYA MENINGKATKAN KEMAMPUAN SISWA MENULIS TEKS BERBENTUK PROCEDURE MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA KELAS IX.6 SMP NEGERI 18 PEKANBARU - WAHYUNI, SRI (Komunitas Manajemen Kompetitif, 2018)
Abstract This study aims to determine the effort to improve students' writing capability in the form of Procedure through Make A Match learning model in class IX.6 in SMP Negeri 18 Pekanbaru. This form of research is a classroom action research with as many as two rounds (Cycle). Each round is done with four stages of planning, implementation, observation and reflection. The subjects of this study are the students of class IX.6 in SMP Negeri 18 Pekanbaru with a total of 40 students consisting of 19 male students and 21 female students. The data obtained in the form of English learning result obtained from the test and observation sheet of teaching and learning activities. Data collection methods used include test, observation and documentation. From the results in the first cycle of student learning outcomes to 30% with inactive classification. While in cycle II result of student in learning experience increase to become 70% with very active classification. This situation shows that improvements in English learning process with Make A Match learning model in English subjects in grade IX.6 students at SMP Negeri 18 Pekanbaru can be said to be fully successful. Keywords : English, Procedure Text, Make A Match